Immunodeficiency: updating the personalized medicine approach to diagnostics and therapeutics. (March 2012) - Buckland, Matthew
The 2011 UK Primary Immunodeficiency Network Forum was held in the Liverpool Arena and Conference Centre. Over 200 healthcare scientists, nurses and doctors were in attendance to discuss a range of issues relating to primary immune deficiencies. This year the biennial forum saw both national and international speakers and a broad representation of posters and oral abstracts from across the interest groups. This article summarizes the keynote lectures and output from 2 days including more than 70 poster presentations and 25 oral presentations.